PERAN MOTIVASI BELAJAR DALAM MEMEDIASI PENGARUH KOMPETENSI PEDAGOGIK GURU, BUDAYA SEKOLAH, DAN STATUS SOSIAL EKONOMI ORANG TUA TERHADAP HASIL BELAJAR BAHASA INGGRIS - Nurlaela; M. Aqil Aziz (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study is based on the low value of English learning outcomes obtained by students. Learning outcomes are influenced by internal and external factors. Internal factors are in the form of learning motivation and external factors are in the form of teacher pedagogical competence, school culture and parents' socio-economic status. The purpose of this study was to test the effect of teacher pedagogical competence, school culture, and parents' socio-economic status on learning motivation and to test the effect of teacher pedagogical competence, school culture, parents' socio-economic status on learning outcomes through learning motivation as a mediating variable. The population in this study were all students at SMP Negeri 1 Bulakamba, with sampling using stratified random sampling technique. Through the Slovin formula, 288 respondents were obtained. The data collection method was carried out by distributing questionnaires and documentation. The data analysis technique used was path analysis with a significance level of 5%. The results of the study showed that teacher pedagogical competence had a positive and significant effect on English learning outcomes by 13.4%, school culture had a positive and significant effect on English learning outcomes by 74.7%, parents' socioeconomic status had a positive and significant effect on English learning outcomes by 32.4%, learning motivation had a positive effect on English learning outcomes by 61.4%. Based on the results of the study, it can be concluded that the variables of teacher pedagogical competence, school culture and parents' socioeconomic status have a positive and significant direct effect on English learning outcomes. The mediating role of the variable learning motivation on teacher pedagogical competence plays a significant and positive role in improving students' English learning outcomes, while the mediating role of learning motivation on school culture and parents' socioeconomic status does not have a significant effect on English learning outcomes.